Productivity Effects and Determinants of the Allocation of Public Infrastructure - Fumitoshi Mizutani; Tomoyasu Tanaka (European Regional Science Association (ERSA), 2005)
Inefficient use of public money is a policy issue of concern in Japan. Some contend that spending towards the formation of public capital does not promote economic growth, one reason being that such investment is concentrated in underdeveloped regions which have a low impact on the growth of economic activity. Investment in underdeveloped regions might be the result of political misallocation or simply the fact that public capital no longer contributes to private productivity. Our study addresses these two important issues: whether or not public infrastructure contributes to production in the private sector, and whether or not political factors really affect the allocation of public infrastructure investment. If the political factors indeed affect allocation, what kinds of political factors are the most deterministic? First, we survey studies on this topic published since the 1970s. For methodology, we plan to take a simultaneous approach to examine these issues. Second, because some data are not publicly available, we construct a data set of public infrastructure and related variables. Public capital in this study is limited to public infrastructure such as roads, ports, airports, banks and dams. Railroads and electric power plants are excluded because these were built by the private sector in Japan. In this study, we plan to use a panel data set covering 46 prefectures and 9 time periods for every 5 years from 1955 to 1995 in Japan. Therefore, the total sample size in this study is 414. Third, after constructing the data set, we overview the regional distribution of public infrastructure and the relationship between public infrastructure allocation and political factors. Last, we estimate simultaneous equations regarding regional production function, infrastructure investment function and grant allocation function. By using these estimated functions, we evaluate whether or not public capital contributes to production and what kind of political factors affect the allocation of public infrastructure investment.
Keywords: 330